Religiosity and risk taking: Is there a demand-side effect? - Berry-Stölzle, Thomas R.; Irlbeck, Steven (Journal of Corporate Finance, 2021)
Religiosity may impact firm risk taking via its risk averse employees or through risk-sensitive demand. Using detailed financial statements of property-liability insurance companies, we find that both religiosity at firms' headquarters and the religiosity of firms' largest geographic market are negatively related to firm risk taking. For firms with one salient market, the impact of market religiosity is approximately the same order of magnitude as headquarter religiosity. Our evidence suggests that firm risk taking is influenced by customer demand.